Footprint reading library video on DVD - Heinle Cengage Learning ([Florence, KY] : Cengage Learning, 2009)
Collection of National Geographic series with footage from National Geographic digital media, divide into 5 main area which is Incredible animals, fascinating places, remarkable people, exciting activities and amazing science
Incredible animals -- Fascinating places -- Remarkable people -- Exciting activities -- Amazing science
Title from container
With video material from National Geographic Digital Media
Executive producer, Curt Fetter ; series editor, Rob Waring ; producer and post editorial, Susan Fetter
Narrated by Mary Clarke (U.K), Paul Clarke (U.K), Laura McCarthy (U.S), David O/Leary (U.S)
DVD format
Optional audio and subtitle in American English or British English
Keywords: National geographic; Geography